Targeted Educational Materials for Sugar-Sweetened Beverage Intervention among Urban Adolescents in Jakarta: A Mixed-Methods Study - Faraji, Mahsa; Wiradnyani, Luh Ade Ari; Chandra, Dian Novita; Februhartanty, Judhiastuty; Wangsa, Andrean; Widyahening, Indah Suci (Jurnal Gizi dan Pangan, 2025)
This study aims to identify the educational needs of urban adolescents in Jakarta to improve their Knowledge, Attitudes, and Practices (KAP) regarding Sugar-Sweetened Beverages (SSBs). Its goal is to develop tailored educational material topics regarding SSBs related to health risks, such as obesity and Non-Communicable Diseases (NCDs). Employing a mixed-methods approach, the research was conducted across five public senior high schools in all five areas of Jakarta from January to February 2024. The quantitative component involved a survey of 488 students to assess their KAP related to SSBs. The KAP formed the basis of the educational materials. The qualitative approach involves 2 Focus Group Discussions (FGDs) with students and 8 In-Depth Interviews (IDIs) with teachers and experts focusing on adolescents’ nutrition and health. The insights were used for the development of the educational materials. The qualitative data were transcribed, coded, and analysed thematically to pinpoint essential educational materials that could bridge the gaps identified in the quantitative data. Results showed that only 18.8% of adolescents had good knowledge, 13.9% had a positive attitude, and 32.4% exhibited healthy practices regarding SSBs. Findings revealed critical issues: poor knowledge, negative attitude, and unhealthy practice regarding the maximum daily sugar intake, inadequate understanding of the nutritional value of sugar, infrequent checking of sugar content before consuming SSBs, limited awareness of SSBs' negative health impacts, and poor knowledge of SSB examples and food labelling practices. Educational materials are needed to address critical gaps in adolescents’ KAP related to SSBs. These materials should focus on raising awareness about the health risks of SSBs, understanding sugar content, improving food labelling literacy, and promoting healthier beverage choices. Future research should assess the implementation and effectiveness of tailored educational strategies to enhance adolescents' KAP related to SSBs, address critical health risks, and promote informed beverage choices.